PENGEMBANGAN ALAT PERAGA SEDERHANA STRUKTUR DAN ORGAN DALAM IKAN UNTUK MEMPERMUDAH PEMBELAJARAN PADA PRAKTIKUM IKHTIOLOGI PERIKANAN - Arief Budiyanto (Jurnal Kelautan, 2015)
Simple structure and organs model of fish used to help students collage in observing fish organ structure in Ichtiology practicum. In fact, there are many observers found difficulties to learn fish organs structure. During the practicum, there are several part of organs that cannot be clearly seen or too small. Moreover, it happened for the fishes that has small size. Another, If the organ structure is not in a good condition it will be difficult to be observed. As a replecement, observer can see dan observe by using tool model to see inside organs of fish. Beside, it make PJMK/Assistant to explain inside part of fish organ structure. Simple structure and organs model of fish is validated by academic civitas that have expertised in fisheries. The result was very worthy to be used in learning process in inchtiology practicum. Score that has been gotten is 100 %. In the class observation, it included 100 observer of Ichtiology. The result of the questionair are: the interesting of fish shape model is 72% was very satisfied.  Model, tool design, accessories and completeness of tool model is 70% was satisfied. The beneficial of the ichtiology praticum is 80% was helped. The corellation of tool and praticum material ichtiology 80%. The suggestion from the tool user in the future, 96%, suggested to use the tool model. Observer comments that mastery assitant in the used of the tool model 65% still less. 70% observer stated that the tool is still need improvement.Keywords: ichtiology practicum, observer, tool model